Corporate Use of Derivatives in Thailand - Tangchitmett, Sasivimon (2005)
This thesis is a study of the results of survey of derivatives use for hedging purposes by 64 non-financial firms in Thailand. The percentage of respondents using derivatives to hedge financial risks is 73 percent. The usage of derivatives is more common among larger firms than among smaller firms. The primary reasons for their use are to manage currency and interest rate exposure. Forwards are the most popular instruments for managing exchange rate exposure, followed by options and swaps. Swaps are most popular for managing interest exposure. Thai firms are most likely focused on reducing fluctuations in cash flows purpose. Transactions costs are the issue of most concern among derivative users. Among those that do not use derivatives, the most important reason is firms do not have significant exposure requiring hedge. Finally, Thai firms do not have well defined policies with respect to derivatives' risk management. A significant number of firms in Thailand seem to be unaware of the need of documented policy covering the use of these instruments and the need of set schedule to report derivatives transactions to the board of directors.